2009
DOI: 10.1158/0008-5472.can-08-2896
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Pathway That Selectively Modulates Apoptosis of Breast Cancer Cells

Abstract: Expression of the nuclear receptor interacting factor 3 (NRIF3) coregulator in a wide variety of breast cancer cells selectively leads to rapid caspase-2–dependent apoptotic cell death. A novel death domain (DD1) was mapped to a 30– amino acid region of NRIF3. Because the cytotoxicity of NRIF3 and DD1 seems to be cell type–specific, these studies suggest that breast cancer cells contain a novel “death switch” that can be specifically modulated by NRIF3 or DD1. Using an MCF-7 cell cDNA library in a yeast two-hy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
55
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 23 publications
4
55
0
Order By: Relevance
“…DIF-1 was found to be identical to interferon regulating factor-2 binding protein 2A (IRF-2BP2A), which had been reported to act as a repressor which mediated the inhibitory effect of IRF-2 on gene expression (3). We found that DIF-1 appears to act as a repressor through Sirt1, a class III histone and protein deacetylase (34). NRIF3/DD1 acts by binding to DIF-1 and reversing the repression mediated by DIF-1 (34).…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…DIF-1 was found to be identical to interferon regulating factor-2 binding protein 2A (IRF-2BP2A), which had been reported to act as a repressor which mediated the inhibitory effect of IRF-2 on gene expression (3). We found that DIF-1 appears to act as a repressor through Sirt1, a class III histone and protein deacetylase (34). NRIF3/DD1 acts by binding to DIF-1 and reversing the repression mediated by DIF-1 (34).…”
mentioning
confidence: 82%
“…Expression of NRIF3 specifically and rapidly leads to caspase-2-dependent apoptosis in breast cancer cells but not other cell types (5,21,34). Time lapse photography documented changes characteristic of apoptosis (5).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…The α-AMA-induced apoptosis is associated with severe liver damage, especially in the early stages of poisoning (18); however, a nonlethal dose of α-AMA prevents DD1 (a novel death domain)-mediated apoptosis by disrupting the protein synthesis. In fact, this process is under investigation in cell culture experiments either alone or in combination with other medicines for the treatment of cancer (19)(20)(21). The cytotoxic effect of β-AMA has been shown in a few studies, but the stability of β-AMA has not been investigated in detail (22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…This result was not consistent with earlier hepatocyte culture studies (2), and the putative reason may be the cell type. It was also reported that α-AMA has antiapoptotic characteristics, which could also be the reason (19,20).…”
Section: Discussionmentioning
confidence: 93%